Prevalence of Onchocerca japonica and O. takaokai infections in the Japanese wild boar, Sus scrofa leucomystax, and the Ryukyu wild boar, S. s. riukiuanus, in Japan. (August 2021) - Uni, Shigehiko; Fukuda, Masako; Uga, Shoji; Agatsuma, Takeshi; Nakatani, Jun; Suzuki, Kazuo; Yokohata, Yasushi; Kimura, Daisuke; Takaoka, Hiroyuki
Abstract: Reports of zoonotic infections with Onchocerca japonica (Nematoda: Filarioidea), which parasitizes the Japanese wild boar, Sus scrofa leucomystax, have recently increased in Japan. To predict the occurrence of infection in humans, it is necessary to determine the prevalence of O. japonica infection in the natural host animals. We investigated the presence of adult worms in the footpads, and of microfilariae in skin snips, taken from the host animals, between 2000 and 2018. Onchocerca japonica was found in 165 of 223 (74%) Japanese wild boars in Honshu and Kyushu. Among the nine regions studied, the highest prevalence of O. japonica infection was found in Oita, Kyushu, where 47 of 52 (90.4%) animals were infected. The ears were the predilection sites for O. japonica microfilariae. Adult worms of O. japonica were found more frequently in the hindlimbs than in the forelimbs of the host animals. Onchocerca takaokai was found in 14 of 52 (26.9%) Japanese wild boars in Oita. In Kakeroma Island among the Nansei Islands, both O. japonica and O. takaokai were isolated from the Ryukyu wild boar, S. s. riukiuanus . These observations could help predict future occurrences of human zoonotic onchocercosis in Japan. Graphical abstract: Unlabelled Image Highlights: Prevalence of Onchocerca species was studied in wild boars from nine areas of Japan. Of 52 Japanese wild boars in Oita, Kyushu, 47 (90.4%) had O. japonica infection. Ears of Japanese wild boars were predilection sites for O. japonica microfilariae. Of 52 Japanese wild boars in Oita, Kyushu, 14 (26.9%) had O. takaokai infection. The Ryukyu wild boar S. s. riukiuanus constitutes a new host record for O. japonica.